2011
DOI: 10.1016/j.tsf.2010.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Mueller matrices for anisotropic metamaterials generated using 4×4 matrix formalism

Abstract: Forward models for the Mueller Matrix (MM) components of materials with relative magnetic permeability tensor 1 µ ≠ are studied. 4 4 × matrix formalism is employed to produce general solutions for the complex reflection coefficients and MMs of dielectric-magnetic materials having arbitrary crystal symmetry and arbitrary laboratory orientation. For certain orientations of materials with simultaneously diagonalizable ε and µ tensors (with coincident principal axes), analytic solutions to the Berreman equation ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Preparing large, high quality samples can be challenging, so effectively all farinfrared ellipsometry measurements have very low throughput. As demonstrated by Kircher et al, 7 high brightness synchrotron radiation overcomes this throughput limit and allows for relatively quick ellipsometric measurements of the samples with a modest cross section area of a few mm 2 . This capability has become increasingly important for researching complex oxides where competing orders drive new physical phenomena (e.g., superconductivity, colossal magnetoresistance, multiferroicity).…”
Section: B U4ir Beamline and The Properties Of The Light Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Preparing large, high quality samples can be challenging, so effectively all farinfrared ellipsometry measurements have very low throughput. As demonstrated by Kircher et al, 7 high brightness synchrotron radiation overcomes this throughput limit and allows for relatively quick ellipsometric measurements of the samples with a modest cross section area of a few mm 2 . This capability has become increasingly important for researching complex oxides where competing orders drive new physical phenomena (e.g., superconductivity, colossal magnetoresistance, multiferroicity).…”
Section: B U4ir Beamline and The Properties Of The Light Sourcementioning
confidence: 99%
“…Several sets of rotating retarders enable a full Muller matrix analysis of anisotropic and bianisotropic samples. The typical spot-size of about 3 × 3 mm 2 at the sample position for the slowly focused synchrotron radiation with f # = 20 allows studying relatively small samples with the surface area of about 1 × 1 mm 2 . In this paper we will describe the instrument in details and will present several examples of the measured rotating analyzer ellipsometry (RAE) and MM spectra of magnetic and ME materials such as Dy 3 Fe 5 O 12 and TbMnO 3 single crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 For the spectra measured at low temperatures, the maximum number of the oscillators used in the fit was N=27. This number does not include the numerous CF and LF transitions below 80 cm -1 that were already described in the previous Section.…”
Section: Experiments In Magnetic Fieldmentioning
confidence: 99%
“…In this case, if the material can be considered as an effective medium, its electromagnetic properties shall be described by several tensors: dielectric permittivity [ε eff ], magnetic permeability [μ eff ], chirality [γ eff ] and [ζ eff ], which have to be retrieved from fitting of the measured SE data (using the Berreman multilayer matrix formalism). Also, it has been suggested that Mueller matrix SE on an effective medium material displaying optical magnetism (i.e., with a nonzero magnetic permeability tensor) is required for separating the magnetic and dielectric contributions to its effective response and recording necessary information for evidencing negative refraction [32]. Note that the effective medium description of metamaterials (and of rough surfaces) is not always legitimate, as evoked in Section 7.…”
Section: Optically Magnetic and Chiral Metamaterialsmentioning
confidence: 99%